1988
DOI: 10.1111/j.1600-0528.1988.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year clinical trial to compare efficacy of dentifrices containing 1.14% and 0.76% sodium monofluorophosphate

Abstract: A 3-yr daily supervised toothbrushing study with a double blind design was conducted to evaluate the anticaries effectiveness of a 1.14% sodium monofluorophosphate (MFP) dentifrice (1500 ppm F) compared to a 0.76% MFP dentifrice (1000 ppm F). This study began with nearly 4000 children, primarily aged 8-11, in grades 3-5, residing in a nonfluoridated community in Florida. A total of 2415 children completed 3 yr of the study, representing 61% of the children who began the study. The results indicate a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…O tamanho do efeito global (valor d) foi de -0,17 (Intervalo de Confiança IC 95% -0,22/-0,12). Três estudos confirmaram a hipótese de que maior concentração de flúor garantiria maior efeito, 7,22,25 enquanto os outros dois não confirmaram essa relação, apesar de apresentarem redução na direção esperada. 21,23 O estudo de Ripa et al 27 foi o único onde a direção dos achados foi em direção oposta ao esperado (valor d=+0,01 IC 95% -0,09/+0,1), ou seja, o grupo com menor concentração de flúor apresentou menor incidência de cárie, apresentando-se não homogêneo.…”
Section: Resultsunclassified
“…O tamanho do efeito global (valor d) foi de -0,17 (Intervalo de Confiança IC 95% -0,22/-0,12). Três estudos confirmaram a hipótese de que maior concentração de flúor garantiria maior efeito, 7,22,25 enquanto os outros dois não confirmaram essa relação, apesar de apresentarem redução na direção esperada. 21,23 O estudo de Ripa et al 27 foi o único onde a direção dos achados foi em direção oposta ao esperado (valor d=+0,01 IC 95% -0,09/+0,1), ou seja, o grupo com menor concentração de flúor apresentou menor incidência de cárie, apresentando-se não homogêneo.…”
Section: Resultsunclassified
“…All the fluoride toothpastes used in this study have anti-caries efficacy as demonstrated in previous caries clinical trials [Conti et al, 1988;Fogels et al, 1988;Stephen et al, 1988]. The dentifrices contained SMFP as the only source of fluoride.…”
Section: Treatment Dentifricesmentioning
confidence: 81%
“…Several caries clinical trials indicate a significant, caries reduction with increasing fluoride concentra tion in the dentifrice used [Conti et al, 1988;Fogels e al., 1988;Hodge et al, 1980;Reed, 1973]. A recen 3-year study [Stephen et al, 1988] investigated th dose response of dentifrices containing SMFP at fluo ride levels of 1,000, 1,500, and 2,500 pg F/g and con eluded that there was a strong correlation with reduc tion of caries increment and increasing fluoride con tent of dentifrices.…”
Section: Discussionmentioning
confidence: 99%
“…It was the first fluoride salt to be included into dentifrice formula. There is strong scientific evidence that MFP reduce caries development [92][93][94][95][96][97][98][99]. The main advantage of MFP is that it can combined with chalk-based abrasives to produce affordable formulations, whereas NaF required inert abrasives such as silica, which is more expensive to produce than the chalk-based formulations.…”
Section: Sodium Mono Uorophosphatementioning
confidence: 99%